Lineage-Specific Biology Revealed by a Finished Genome Assembly of the Mouse - Church, Deanna M.; Goodstadt, Leo; Hillier, LaDeana W.; Zody, Michael C.; Goldstein, Steve; She, Xinwe; Bult, Carol J.; Agarwala, Richa; Cherry, Joshua L.; DiCuccio, Michael; Hlavina, Wratko; Kapustin, Yuri; et al. (PLOS Biology, 2009)
A finished clone-based assembly of the mouse genome reveals extensive recent sequence duplication during recent evolution and rodent-specific expansion of certain gene families. Newly assembled duplications contain protein-coding genes that are mostly involved in reproductive function.